DAMPAK KEBERADAAN TEMPAT PEMBUANGAN AKHIR (TPA) SAMPAH TERHADAP KEADAAN SOSIAL EKONOMI PEMULUNG DI DESA TANJUNG SELAMAT KECAMATAN SUNGGAL KABUPATEN DELI SERDANG - Lara Anjelita Tarigan; Sintong, Mahara (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2024)
This research aims to determine the impact of the existence of a final waste disposal site on the socio-economic conditions of the community in Tanjung Selamat Village, Sunggal District, Deli Serdang Regency. The method in this research is descriptive qualitative data obtained by observing and interviewing respondents.The results of the research show that: The positive impact caused by the existence of this final waste disposal site on the socio-economic conditions of scavengers who work at the final waste disposal site is very helpful for the waste scavengers who are able to create employment opportunities for the waste scavengers and increase their income both in meeting their daily needs. day and to send their children to school, there are even scavengers who send their children to college from the results of their scavenging for years, but there are also negative impacts caused by the presence of landfills, including some of the scavengers have suffered from fever. bleeding, typhus and itching. Apart from being susceptible to disease from Qada and waste scavengers, they also have poor air quality in their homes, this is due to the presence of garbage trucks passing by which can contribute to dust, smoke and unpleasant odors.